Internalizing problems and suffering due to sensory symptoms in children and adolescents with and without autism spectrum disorder - Tsuji, Yurika; Imaizumi, Shu; Sugawara, Masumi; Oiji, Arata (Frontiers in Psychology, 2022)
Sensory symptoms are common in autism spectrum disorder (ASD). Previous studies have shown a positive correlation between sensory symptoms and internalizing problems; however, the role of the suffering due to sensory symptoms is not well understood. In the present study, we hypothesized that the relationship between sensory symptoms and internalizing problems in children is mediated by children’s and surrounding people’s suffering due to sensory symptoms. Parents of 113 students aged 6–15 years with and without ASD completed questionnaires about their children’s autistic traits, sensory symptoms, suffering due to sensory symptoms, and internalizing problems. The results showed that autistic traits and sensory symptoms were distributed as a continuum throughout children with and without ASD. Therefore, we investigated the relationship among variables in children with and without ASD attending regular classes. Structural equation modeling indicated that those who scored higher on sensory symptoms demonstrated greater suffering due to sensory symptoms as predictors of internalizing problems. Our findings provide evidence for developing a support system that specifically reduces suffering due to sensory symptoms, especially for students in regular classes.